Scaling Gender Equality and Social Inclusion in Schools Through Stakeholder Mapping: Teachers’ Perspectives on Enablers and Barriers - Kinley Seden (Journal of Research in Education and Pedagogy, 2025)
Stakeloder engagement is crucial for driving Gender equality and social inclusion (GESI) initiatives. Using Participatory Action Research, this situational analysis (SAS) study explored people, place, and things catergorised into four scaling groups: initiators, enablers, competitors, and the impacted for scaling GESI initiatives in schools and communities effectively through stakeholder engagement. The research during the participation axis phase administered a survey questionnaire to teachers, including five males and females, to analyse stakeholders responsible for promoting GESI in schools. Key findings revealed that Initiators, such as school leaders and educators, played a crucial role in driving GESI-related changes within schools. Enablers, including local community leaders and supportive teachers, were instrumental in ensuring the successful implementation and sustainability of GESI initiatives. However, challenges arose from Competitors, including senior citizens, religious practitioners, and some local leaders, whose conservative beliefs often impeded progress. The Impacted group, consisting of marginalized students, teachers, and women affected by gender inequality, was identified as the primary beneficiary of successful GESI initiatives. Despite its valuable insights, the study has a few limitations. The perspectives gathered were primarily from teachers, which may not fully capture the views of all relevant stakeholders, particularly those from marginalized groups or other community members. Additionally, the categorization of stakeholders, especially within the Competitors and Impacted groups, may lack sufficient nuance in certain contexts. The study recommends a more inclusive stakeholder engagement process that involves all groups, including Competitors, through participatory dialogue to address resistance and foster collaborative solutions. Continuous capacity-building efforts for teachers, school leaders, and policymakers are essential to ensure the sustainability of GESI initiatives. Future research should expand the analysis to include a broader range of stakeholders and account for regional variations in the implementation of GESI initiatives.